Characteristics of Physical, Microbiological, and Organoleptic of Dali and Fresh Cheese from Goat’s Milk during Low Temperature Storage - Wahyuningtyas, Amalina Nur; Fezra, Haiwal; Taufik, Epi; Soenarno, Mochammad Sriduresta; Nurmasytha, Andi (Jurnal Agroekoteknologi dan Agribisnis, 2025)
Indonesian food culture is known for its diversity in various aspects, including traditional Indonesian food. Livestock products such as meat and milk are ingredients that Indonesian people often use to make traditional food. The milk that is considered to have better digestibility and lower allergy potential is goat's milk. In addition, goat's milk can be processed as a carrier for functional ingredients, such as prebiotic ingredients or probiotic bacteria, into various products. Dali is one of Indonesia's traditional foods. North Sumatra has a fresh cheese called dali. Alo-alo leaves (Agave angustifolia) are an ingredient used in the coagulation process in making dali. This study aims to examine the physical, microbiological, and organoleptic characteristics of dali by using a coagulant of Agave angustifolia leaf juice and fresh cheese with commercial rennet coagulant during low-temperature storage. This research was carried out for 12 days and every 4 days pH, Total Plate Count (TPC), and organoleptic tests were observed, resulting in data on fresh dali and cheese H0, H4, H8, and H12 with low temperature storage. This research design was carried out in 3 replications and analyzed using the T-test to obtain TPC and pH data, while for organoleptic data using Kruskal-Wallis. The results of the analysis on the Total Plate Count (TPC) of dali and fresh cheese showed a significant difference (P<0,05), namely on day 0, while the pH test of dali and dangke showed a significant difference (P<0,05) on day 0 and 4th. Panelists preferred fresh cheese over Dali, based on organoleptic test results.